1971
DOI: 10.1002/1520-6807(197101)8:1<29::aid-pits2310080107>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Schenectady Kindergarten Rating Scales and first grade achievement and adjustment

Abstract: 29may be sufficient to present only positive instances. Negative instances, either related or unrelated, may produce more efficient learning when only one type of positive instance is used. REFERENCES AUSUBEL, DAVXD. Mear ingful reception learning and the acquisition of mnce ts. In H. Klausmeier and C. Harris (Eds), Analyses of m e p t learning. New York: Academic Ikm, 1966. BRALEY, LOY 5. Strategy selection and negative instances in concept learning.The Schenectady Kindergarten Rating Scales (SKRS) are a batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Correlations between the ratings and reading achievement in grades 2 through 5 ranged from .45 to .69. Other investigators (e.g., Bryan & Mc-Grady, 1972;Tobiessen, Duckworth, & Conrad, 1971) have developed batteries of scales for predicting achievement, assuming that ratings on a number of scales would offer greater information than would a single, global rating. An example of this approach is the extensive study by Feshbach, Adelman, and Fuller (Note 1), who obtained teacher ratings on 41 characteristics of over 1,500 kindergarten children.…”
mentioning
confidence: 99%
“…Correlations between the ratings and reading achievement in grades 2 through 5 ranged from .45 to .69. Other investigators (e.g., Bryan & Mc-Grady, 1972;Tobiessen, Duckworth, & Conrad, 1971) have developed batteries of scales for predicting achievement, assuming that ratings on a number of scales would offer greater information than would a single, global rating. An example of this approach is the extensive study by Feshbach, Adelman, and Fuller (Note 1), who obtained teacher ratings on 41 characteristics of over 1,500 kindergarten children.…”
mentioning
confidence: 99%
“…Tobiessen et al (1971) found the Schenectady Kindergarten Rating Scales moderately useful in predicting the performance of children in grade 1 who were likely to have learning and impulse control problems. Pate and Webb (1966) published a group test that is reported to identify young children with potential learning problems.…”
mentioning
confidence: 99%